TO IDENTIFY MEDICATION ERRORS IN TREATMENT CHART IN PEDIATRIC AND MEDICINE UNITS OF A TERTIARY CARE TEACHING HOSPITAL IN DAVANGERE - OINAM JIMMY DEVI,; M K NIKHITHA,; VINAY B C,; PATEL SUNIL B, (International Journal of Pharma and Bio Sciences, 2015)
The research was carried out to study the medication errors in the treatment chart of the patients who were admitted in the pediatrics and medicine units of a tertiary care teaching hospital in Davangere. A total 100 cases were collected in which 124 medication errors were identified, among 124 medication errors 51(41.12%) were drug given without indication, 19(15.32%) were drug duplication, 31(25%) were over dose, and 23(19%) were under dose. The study shows that the age group of 1 month to 5 years was having maximum number of medication errors, i.e. 44.35% in which maximum number drug given without indication was found to be 33.34%. Improper dose includes over dose 80.64% and under dose, 69.56% were identified more in the pediatric unit than medicine unit. 63.16% of drug duplication were found in medicine unit than in pediatric unit which was 36.84%.